Optimization of Flat Construction Implementation Time Using Critical Path Method and Project Evaluation and Review Technique - Adis Harni Tuanaya; Venn Yan Ishak Ilwaru; Yopi Andry Lesnussa (Pattimura International Journal of Mathematics (PIJMath), 2024)
This research aims to develop a system that effectively solves construction project management problems using PERT (Project Evaluation and Review Technique) and CPM (Critical Path Method) methods for the ASN flat construction project in Piru City, Maluku Province, Indonesia. In this study, the project activity data was analyzed using the PERT Method, which includes realistic, optimistic, and pessimistic durations; then, it is used to calculate the estimated time of each activity. Meanwhile, CPM was used to determine the critical path of the project. The results showed that project management can be done more accurately and efficiently with these two methods, minimizing the risk of delays. The optimal duration of the project obtained is 49 weeks with a probability value of 98.87% with the critical path obtained, namely A-B-E-F-G-J-K-L-M.